Factors influencing the behavioral intention of muslim students in Indonesia to contribute to cash-waqf through mobile wakaf uang Nu BTN - Dede Denis (Fak. Ekonomi dan Bisnis Islam UIN Sunan Kalijaga, 2018)
yt 1./ws.c.1